2000
DOI: 10.1038/sj.ijo.0801366
|View full text |Cite
|
Sign up to set email alerts
|

Pro12Ala mutation in the peroxisome proliferator-activated receptor γ2 (PPARγ2) and severe obesity: a case–control study

Abstract: OBJECTIVE: To explore the association of the Pro12Ala mutation in the peroxisome proliferator-activated receptor g g g2 with severe obesity and the features of the metabolic syndrome in a population-based sample of Caucasians. PARTICIPANTS AND METHODS: The study is based on a case ± control design: 95 non-diabetic severely obese (body mass index, BMI b 35 kgam 2 ) cases and 280 normal weight (BMI`25 kgam 2 ), age-and sex-matched controls selected from the same population were studied. Height, weight, waist cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Several studies have reported an association between Ala and increased insulin sensitivity and reduced risk of T2D (13,14), as confirmed by meta-analysis (15). However, other studies failed to find an association between Pro12Ala and obesity and insulin sensitivity (16,17). The allelic frequency of the Ala allele is divergent among different ethnic groups, with a range from 0.12 in Caucasian Americans to 0.03 in African Americans and 0.01 in Chinese (18).…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have reported an association between Ala and increased insulin sensitivity and reduced risk of T2D (13,14), as confirmed by meta-analysis (15). However, other studies failed to find an association between Pro12Ala and obesity and insulin sensitivity (16,17). The allelic frequency of the Ala allele is divergent among different ethnic groups, with a range from 0.12 in Caucasian Americans to 0.03 in African Americans and 0.01 in Chinese (18).…”
Section: Introductionmentioning
confidence: 90%
“…Although the Ala12 allele was initially associated with lower BMI (36), this association turned out to be inconsistent in further studies (37)(38)(39)(40). Three different meta-analyses have been conducted to assess the relation between the Pro12Ala polymorphism and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between Ala12, increased insulin sensitivity and a reduced risk of type 2 diabetes [17-20] which has been supported by meta-analysis [17]. However, results assessing the risk of the Pro12Ala in obesity were controversial [21,22]. …”
Section: Introductionmentioning
confidence: 99%